2004
DOI: 10.1063/1.1829037
|View full text |Cite
|
Sign up to set email alerts
|

Rotational dynamics of methyl groups in m-xylene

Abstract: Methyl group dynamics of m-xylene was investigated by using incoherent inelastic and quasi-elastic neutron scattering. Inelastic measurements were carried out at the high flux backscattering spectrometer HFBS at the National Institute of Standards, quasi-elastic measurements at the time-of-flight spectrometer NEAT at the Hahn-Meitner-Institute. Rotational potentials are derived which describe the tunnel splittings, first librational, and activation energies of the two inequivalent CH 3 groups. Indications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
4
7
0
2
Order By: Relevance
“…The coupling between the methyl rotors has been discussed in numerous works on the IVR of xylenes. It has been found that, in general, substitution by methyl groups accelerates the IVR process because of the interaction of the methyl rotors with the ring and with each other . This suggestion is consistent with the observation in the EI spectra that R is lower for p ‐xylene, for which the methyl groups can be thought of as uncoupled.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The coupling between the methyl rotors has been discussed in numerous works on the IVR of xylenes. It has been found that, in general, substitution by methyl groups accelerates the IVR process because of the interaction of the methyl rotors with the ring and with each other . This suggestion is consistent with the observation in the EI spectra that R is lower for p ‐xylene, for which the methyl groups can be thought of as uncoupled.…”
Section: Resultssupporting
confidence: 84%
“…The role of methyl substitution and internal rotation in the acceleration of intramolecular vibrational redistribution (IVR) has attracted the interest of researchers for many years . Hyperconjugation and van der Waals interactions between the methyl rotor and the ring are believed to induce coupling between several normal vibrational modes, which thus leads to faster IVR processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to discussions in Ref. 23, a more complex transition scheme combined with dispersion could result in less pronounced librational peaks, and a further suppression of intensity could occur via the above-mentioned damping. The coupling model also yields transitions in the range of 16-18 meV, and these additional features as well as the magnitude of the splitting would not contradict the experimental DOS ͑Fig.…”
Section: Ch 3 F Mode Dampingsupporting
confidence: 66%
“…In addition, a slight asymmetry of the peak can be seen although this certainly less pronounced as in a previous study of m-xylene. 17 In order to obtain a value of the split of the tunneling sublevels three Lorentzians, representing the AA → AE, AA → E a E b , and AA → E a E a transitions with relative intensities 2:1:1 should be used. Due to the slightly worse than expected instrumental resolution ͑see above͒ in combination with the expected small difference of only 0.02 eV between the AA → E a E b and AA → E a E a transitions we were not able to describe both transitions separately.…”
Section: Resultsmentioning
confidence: 99%